Use of the Buffering Capacity of the Building Envelope for the Reduction of the Rate of Air Exchange. (November 2015) - Slimani, Zakaria; Trabelsi, Abdelkrim; Virgone, Joseph; Belarbi, Rafik; Djedjig, Rabah
Abstract: This work addresses the use of humidity controlled ventilation with high buffering capacity building envelope. The humidity controlled ventilation rate is associated to the level of moisture in rooms. This paper fits into the idea of reducing the building energy consumption by reducing the duration of air ventilation rate which is usually quite high. This solution is not without consequences on building because it presents a risk of deterioration of indoor air quality (e.g. non evacuation of VOC) and apparition of mold. This paper aims to enhance water inertia of building walls in order to reduce the ventilation rate and study the risk associated with moisture excess. It is achieved for different scenarios of in-house production of vapor which can be met in reality and for different cases.